(untitled) (Comparative & International Education Series, 2021)
There has been an exponential growth in Chinese international students (CISs) pursuing postsecondary degrees in the U.S. in the past decade. More knowledge on how CISs’ engagement differs from that of U.S. students is strongly needed. Using a large-scale and multi-institutional survey data, this study first examined CISs’ engagement in employing effective learning strategies, collaborative learning, and student-faculty interaction at U.S. four-year colleges and universities. Then, the extent to which CISs’ engagement in these activities differs from that of U.S. domestic students was explored. Given these engagement behaviors may be influenced by culture, Hofstede’s Dimensions of Culture was used as the conceptual grounding. This study helps enhance mutual understandings of engagement between CISs and U.S. students and provides recommendations to faculty and practitioners in supporting the cross-cultural integration and mutual engagement of CISs and U.S. students.